Characteristics of gelling and water holding properties of hen egg white/yolk gel with NaCl addition. (April 2018) - Li, Junhua; Li, Xin; Wang, Chenying; Zhang, Mengqi; Xu, Yali; Zhou, Bei; Su, Yujie; Yang, Yanjun
Abstract: The effects of NaCl addition on the gelling and water holding properties of egg white/yolk gels were studied via solubility, surface hydrophobicity, reduced sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), Fourier transform infrared spectra (FTIR), textural analysis, low-field nuclear magnetic resonance (LF-NMR) and centrifugation. Results showed that more solubility and surface hydrophobicity increase of egg yolk dispersions were observed than that of egg white dispersions. SDS-PAGE results indicated that the different change trend of surface hydrophobicity between two egg proteins was closely related with the dissociation of egg yolk granule proteins. NaCl-induced protein heat denaturation will result in the decrease of ordered secondary structure (α-helix and β-sheet) by breaking hydrogen bond for both egg protein gels. A rapid decrease ( p  < 0.05) in fracture strength/strain of egg white gels was found as the NaCl increased, while the fracture strength/strain of egg yolk gels first rose and then descended, indicating that the significant increases of solubility and hydrophobicity of egg yolk dispersions at a certain NaCl concentration (≤1.8%) were benefit to the formation of strong molecule interaction among gel network. Results from LF-NMR and centrifugation water holding capacity (WHC) tests revealed that NaCl addition affected the WHC of egg white gels by increasing the mobility and distribution of free water, and had a complex influence on proton mobility and relaxation peak changeability of egg yolk gels due to the interaction among lipid, protein and water. Graphical abstract: Image 1 Highlights: Effect of NaCl on the gelling properties of egg white/yolk dispersions was studied. NaCl resulted in the decrease of ordered secondary structure for egg protein gels. Gel texture changes of egg white/yolk were related with inter-force balance. Low field NMR and centrifugation can reflect WHC from different angles.